Kinetic and Kinematic analysis of ACL reconstruction in association with lateral-extrarticular tenodesis of the knee in revision surgery: a pilot study - Di Benedetto, Paolo; Buttironi, Michele Mario; Mancuso, Francesco; Roman, Federico; Vidi, Daniele; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2021)
BackgroundAnterior cruciate ligament reconstructions are a very frequent surgery. The key role of the anterolateral ligament in the knee rotational stability has been undelighted in recent years. Extra-articular tenodesis in association with ACL reconstructions, serves to eliminate anterolateral rotatory instability. The aim of our study is to compare treated knees with the contralateral uninjured knee in those cases whom been treated with ACL arthroscopic reconstruction and lateral extra-articular tenodesis in revision surgery, and evaluate clinical results with kinematic and kinetic examinations methods.Materials and methodsSixteen patients (10 males and 6 females) with ages from 21 to 37 had been treated at the Orthopaedic Clinic of Udine for failure of previous ACL reconstruction. In all patients was performed ACL arthroscopic reconstruction with the association of a lateral extra-articular tenodesis (Coker-Arnold). We have decided to asses the patients at one year after surgery with GNRB arthrometer and Bioval inertial sensor system.ResultsAll patients treated with arthroscopic ACL reconstruction and lateral extra-articular tenodesis have regained pre-injury sagittal knee stability and gait dynamics.